1st case - Patterson, James, 1947-; Tebbetts, Christopher (Little, Brown and Company, 2020)
"Recruited into the FBI when her unorthodox programming skills get her kicked out of MIT, a computer genius tracks a killer who has been targeting young women through a sophisticated messaging app."--